New records of Agaricales (Fungi) from Mexico - Chacon, Santiago (Instituto de Ecología, A.C., 1995)
Two new records of Agaricales, Campanella elongatispora and Russula mephitica for Mexican mycobiota are given. The fungi were collected in a subtropical forest of Veracruz State.